The Research on Human Resources Competences Necessary for Sustainable Organizational Success - Kumar N K, Ajesh (Digital Repository of Theses, 2025)
Human Resources is a field that constantly needs to adjust to keep up with the changing needs of organisations, especially in the face of global challenges such as the pandemic. This thesis examines the current competencies and operational approaches of Human Resources professionals, as well as the new functional and leadership qualities required for organisational resilience and success in the business the environment following the pandemic. The Human Resources field has undergone five distinct phases of development, transitioning from a job focused on basic care and maintenance to one that actively contributes to strategic business decisions. Currently, Human Resources is embarking on a new era of transformation. Historically, Human Resources operations have existed since ancient times, encompassing the selection of ethnic group leaders and the establishment of safety protocols. Over time, employees have transitioned from being seen as simple parts of the industrial economy to being recognised as crucial assets in the knowledge economy and champions for sustainability in the twenty-first century. The historical setting underscores the necessity for Human Resources professionals to adopt innovative leadership styles, mindsets, and competencies to build sustainable companies. Although technological developments are important, they alone are not enough to accomplish corporate objectives. Resilient Human Resources professionals play a crucial role in enabling rapid and favourable organisational transition in a constantly evolving environment. Several research and consulting institutions, as well as Human Resources scholars, have put forward a multitude of functional and cognitive abilities that are essential for the modern working environment. Nevertheless, these skills, which are frequently described using various terms, have not been methodically ranked in order of importance. This study aims to address this gap by emphasising the essential leadership styles, mindsets, and skill sets required for Human Resources professionals. The results will offer a comprehensive structure for the evolution of Human Resources, allowing organisations to quickly adjust to economic challenges and attain sustainable success in the future workplace and business environment.